Thymoquinone, the Most Prominent Constituent of Nigella Sativa, Attenuates Liver Damage in Streptozotocin-Induced Diabetic Rats via Regulation of Oxidative Stress, Inflammation and Cyclooxygenase-2 Protein Expression - Saleh A. Almatroodi; Abdullah M. Alnuqaydan; Mohammed A. Alsahli; Amjad Ali Khan; Arshad Husain Rahmani (Applied Sciences, 2021)
Diabetes mellitus (DM) is a multifaceted metabolic disorder that results in dysfunction and failure of various organs. The present study aimed to evaluate the role of Thymoquinone (TQ), on antidiabetic, oxidative stress, and anti-inflammatory activities in streptozotocin (STZ)-induced (55 mg/kg b.w) diabetic rats. TQ was orally given for 8 consecutive weeks at dose of 150 mg/kg b.w. The blood glucose, insulin, total cholesterol, triglycerides, liver function enzymes, high density lipoprotein (HDL)-cholesterol, and low-density lipoprotein (LDL)-cholesterol levels were measured accordingly in control, diabetes control (DC), and TQ-treatment groups. These experiments confirmed that TQ conserves the insulin level (0.4 ng/mL vs. 0.23 ng/mL), fasting blood glucose (146 ± 7 mg/dL vs. 225 ± 5 mg/dL), and HbA1c (7.5% vs. 10.6%) quite considerably as compared to DC animals. Our results also confirmed that TQ treatment conserves the body weight and lipid profile significantly in STZ-treated animals as compared to the DC group. Moreover, the antioxidant enzymes (GSH, SOD, GST, and CAT) levels decreased, liver function enzymes (ALT, AST, and ALP), lipid peroxidation and inflammatory markers (TNF-α, CRP, IL-1β, IL-6) increased by STZ treatment, that is significantly restored after TQ treatment. As compared to untreated animals, TQ restored the hepatocytes architectural changes and collagen fibers and cox-2 protein expression in liver tissues as evaluated by hematoxylin and eosin, Masson’s trichrome, and immunohistochemistry staining. Taken together, all these findings indicated that TQ ameliorates glucose level and lipid metabolism. It restores liver function, antioxidant enzymes, anti-inflammatory markers, and maintains hepatocytes architecture in STZ-induced diabetes mellitus rats. Here, in this study, we have demonstrated for the first time the role of TQ in the reduction of the expression of cyclooxygenase-2 and fibrosis formation in diabetic rats. Based on the findings, the study suggests that TQ is a novel natural drug with a wide range of clinical applications including the management of diabetes mellitus.